Penguatan Kompetensi Pedagogik Guru Madrasah Ibtidaiyah dalam Mengintegrasikan Teknologi Digital pada Pembelajaran Abad Ke-21 - amynizzah, liefya (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to examine the development of digital literacy among Madrasah Ibtidaiyah (MI) students through innovative pedagogical approaches in response to 21st-century learning demands. The study is grounded in the low level of students' digital literacy and teachers' pedagogical competence in integrating technology. This research employs a qualitative approach using library research by analyzing relevant academic sources. Data were analyzed through content analysis, including data collection, reduction, and interpretation. The findings reveal that students' digital literacy remains at a basic level and is not optimally utilized in learning processes. In addition, teachers’ pedagogical competence is constrained by limited training, understanding, and technological infrastructure. The implementation of Project-Based Learning and Problem-Based Learning is considered effective in enhancing digital literacy, critical thinking skills, and character development among students.